Вплив постмодерну на сучасні медіа - Попіль, Дарина (Видавництво Львівської політехніки, 2017)
The paper discusses the situation of modern journalism in the context of postmodern era. The influence of the main features of the postmodern era on television and online journalism is analyzed.
Keywords: journalism; media; postmodern; mass culture; pluralism; information